Kinetic study of time-dependent fixation of UVI on biochar - Ashry, Ahmed; Bailey, Elizabeth H.; Chenery, Simon; Young, Scott D. (Elsevier, 2016)
Biochar, a by-product from the production of biofuel and syngas by gasification, was tested as a material for adsorption and fixation of UVI from aqueous solutions. A batch experiment was conducted to study the factors that influence the adsorption and time-dependent fixation on biochar at 20oC, including pH, initial concentration of UVI and contact time. Uranium (UVI) adsorption was highly dependent on pH but adsorption on biochar was high over a wide range of pH values, from 4.5 to 9.0, and adsorption strength was time-dependent over several days. The experimental data for pH > 7 were most effectively modelled using a Freundlich adsorption isotherm coupled to a reversible first order kinetic equation to describe the time-dependent fixation of UVI within the biochar structure. Desorption experiments showed that UVI was only sparingly desorbable from the biochar with time and isotopic dilution with 233UVI confirmed the low, or time-dependent, lability of adsorbed 238UVI. Below pH 7 the adsorption isotherm trend suggested precipitation, rather than true adsorption, may occur. However, across all pH values (4.5–9) measured saturation indices suggested precipitation was possible: autunite below pH 6.5 and either swartzite, liebigite or bayleyite above pH 6.5.